2014
DOI: 10.1371/journal.pone.0106330
|View full text |Cite
|
Sign up to set email alerts
|

OFD1 and Flotillins Are Integral Components of a Ciliary Signaling Protein Complex Organized by Polycystins in Renal Epithelia and Odontoblasts

Abstract: Mutation of the X-linked oral-facial-digital syndrome type 1 (OFD1) gene is embryonic lethal in males and results in craniofacial malformations and adult onset polycystic kidney disease in females. While the OFD1 protein localizes to centriolar satellites, centrosomes and basal bodies, its cellular function and how it relates to cystic kidney disease is largely unknown. Here, we demonstrate that OFD1 is assembled into a protein complex that is localized to the primary cilium and contains the epidermal growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…As a known cilia protein [ 49 ] but no report in retina tissue, our results showed that Ofd1 was localized to the photoreceptor outer segments as shown by immunostaining in rat retina. Retina connecting cilium connects the inner and outer segments of the photoreceptor, mediating bi-directional transport of phototransducing proteins required for vision.…”
Section: Discussionsupporting
confidence: 46%
“…As a known cilia protein [ 49 ] but no report in retina tissue, our results showed that Ofd1 was localized to the photoreceptor outer segments as shown by immunostaining in rat retina. Retina connecting cilium connects the inner and outer segments of the photoreceptor, mediating bi-directional transport of phototransducing proteins required for vision.…”
Section: Discussionsupporting
confidence: 46%
“…The function of PKD2 is suppressed by PtdIns(4,5)P 2 . [98] The interaction between EGFR and PKD2 may be involved in the mechanosensation that is necessary for directed migration of these cells. [85,93] Therefore, EGF signaling can sensitize the primary cilium-based mechanosensation by reducing the threshold of PKD2 for activation by mechanical stimulation.…”
Section: Egf Signaling Regulates Mechanosensation Through Primary Ciliamentioning
confidence: 99%
“…New mechanisms whereby non-cilia associated proteins impact cilia structure and function have been identified [29, 33]. The interactions of diverse cilia-associated cystic kidney disease proteins continue to be investigated, with an expanding list of proteins that comprise the polycystin cilia signaling complex [36, 37]. A new technique to directly measure cilia calcium concentrations and channel activity demonstrated that cilia have a separate calcium signaling microenvironment modulated by a unique calcium channel [30, 31].…”
Section: Resultsmentioning
confidence: 99%
“…Jerman et al [37] found that OFD1 is part of the large signaling complex that contains PC1, PC2, EGFR, and flotillins. In human ADPKD cells, they further showed that loss of PC1 cilia localization was associated with loss of cilia localization of the other protein complex members.…”
Section: Recent Insights and Controversiesmentioning
confidence: 99%